Highly Efficient Extraction of Aromatic Compounds from Houttuyniacordata thumb by Cryogenic Grinding Techniques - Xue, Qingsong (International Journal of Biotechnology for Wellness Industries, 2013)
The current study was focused on the extraction of essential oil from Houttuyniacordata thunb (HCT) by using different solvents (ethyl acetate, ethanol, and n-hexane) using cryogenic grinding techniques (CGT). The influence of the storage time of the HCT extract on the volatile components was investigated. This paper also discussed and interpreted the mass spectral fragmentation patterns for the three new compounds (undenoyl acetaldehyde, dodenoyl acetaldehyde, and decyl-imine acetaldehyde). The results showed that the extractability of essential oil obtained by CGT using ethyl acetate as an extractant was as high as 1.14% and the content of decanoyl acetaldehyde in the essential oil was as much as 55.96%, much higher than the previously reported values. It was suggested that the oxidation and decomposition of those unstable components were effectively reduced when the essential oil was extracted by CGT. The content of decanoyl acetaldehyde in the HCT extractant remained constantly when using ethyl acetate as a solvent in the process of storage, while using ethanol as a solvent, the content of decanoyl acetaldehyde decreased rapidly as the storage time increased. The author proposed that the ethanol reacted with decanoyl acetic acid and formed decanoyl acetic ether, which accelerated the decomposition of the decanoyl acetaldehyde